Caribbean and the North American Free Trade Agreement {NAFTA} (UN. ECLAC Port of SpainTT, 1992)
Examines the terms of the Agreement in the light of their implications for, and possible impacts on, member countries of the Caribbean Development and Cooperation Committee. Reviews also the implications for the members in the light of attempts to deepen their integration movement and to agree upon Common External Tariff levels, and their commitments to other trade and investment arrangements under the Lome Convention and CARIBCAN.
DC